2005
DOI: 10.1159/000085958
|View full text |Cite
|
Sign up to set email alerts
|

The Nasal Airflow in Noses with Septal Perforation: A Model Study

Abstract: Background: Septal perforation is a common clinical problem in rhinology. Affected patients suffer from a dry nose, crusts as well as recurrent epistaxis and sometimes an inspiratory whistle. The aim of this study was to investigate the underlying flow dynamic mechanisms. Methods: The physical flow effects of such pathologies were examined in functional nose models (box models) and anatomically exact models of the nose. Therefore, septal perforations of different sizes and localisations were studied in straigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 20 publications
3
43
1
1
Order By: Relevance
“…The accelerated airflow would reduce the contact time of airflow on the mucosa and increased wall shear stress would augment the stimulation of airflow to the nasal mucosa, both of which would damage the physiological function of the nasal cavity. Both Lee et al [6] and Grutzenmacher et al [7] considered that the impact of airflow communication in septum perforation correlated with the size but not the location of perforation. However, their researches were limited to the anteroposterior direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accelerated airflow would reduce the contact time of airflow on the mucosa and increased wall shear stress would augment the stimulation of airflow to the nasal mucosa, both of which would damage the physiological function of the nasal cavity. Both Lee et al [6] and Grutzenmacher et al [7] considered that the impact of airflow communication in septum perforation correlated with the size but not the location of perforation. However, their researches were limited to the anteroposterior direction.…”
Section: Discussionmentioning
confidence: 99%
“…The high wall shear stress is always located in the posterior region of perforation, which could explain drying and epistaxis. Several perforation models with different sizes and locations have been investigated, and it has been confirmed that the devastating symptoms are correlated with the size of perforation but not with location [6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…But despite the wide range of techniques proposed for the only curative alternative, which is surgical, the results are not always satisfactory as is clear from the different procedures recorded in the literature (Warren et al, 1987;Schendel and Carlotti, 1991). Therefore, the main therapeutic approach is preventative, involving early detection, given that the main cause of septal perforation is surgery of the nasal septum, followed by the use of nasal decongestion sprays and intranasal steroids that are widely used to relieve symptoms after surgery involving nasal congestion and breathing difficulties (as it is the case in the immediate postoperative period following orthognathic surgery) (Grützenmacher et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…From then on different authors have studied the effects on nasal airflow through rhinomanometry, acoustic rhinometry, fluid dynamic experiments and functional nasal models (Schendel and Carlotti, 1991;Erbe et al, 2001;Grützenmacher et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…10 These authors assessed septal perforations of varying sizes and locations, with and without septal deviation. Streamlines were found to 'bump' towards the posterior border of the perforation, causing turbulence which increased with increasing perforation size.…”
Section: Introductionmentioning
confidence: 99%